Kepewarisan Nilai Budaya dalam Mite Silampari Sebagai Folklor Lisan pada Masyarakat - Nur Nisai Muslihah; Rusmana Dewi (Jurnal Kajian Bahasa, Sastra dan Pengajaran (KIBASP), 2020)
This study aims to describe the inheritance of cultural values ​​in Mite Silampari as an oral folklore in Lubuklinggau City. This study uses a quantitative descriptive approach, using data in the form of cultural values ​​contained in Mite Silampari which is a folklore of the City of Lubuklinggau which includes the essence of human life (MH); the nature of human work (MK); human relations (MM); the nature of human time (MW); and the nature of human nature (MA). Data on the inheritance of cultural values ​​in Mite Silampari was obtained through a questionnaire distributed to 50 respondents who were analyzed using the percentage formula. From the results of data analysis, it is known that the dominant cultural value in Mite Silampari is the Nature of Human Work (MK) in the form of cultural values ​​Noticing the Kinship System (84%) answered MBD, followed by the form of Honesty cultural values ​​(80%). Next is the cultural value of Relations between Humans in the form of the Cultural Value of Building Friendship (70%). Thus, the inheritance of cultural values ​​in Mite Silampari as oral folklore in the community in Lubuklinggau City is in the Good category (78%) because it is in the range 68 - 83 / Good. In conclusion, the level of value inheritance in the Mite Silampari culture as oral folklore in the community in Lubuklinggau City is classified as good. Keywords: Inheritance, Cultural Values, Mite Silampari, Oral Folklore